Antifibrinolytics for the initial management of sub arachnoid haemorrhage. Issue 4 (23rd March 2005) - Carley, Simon; Sen, Ayan
Abstract : A short cut review was carried out to gather the evidence for and against the use of tranexamic acid to patients who have suffered subarachnoid bleeding. 267 papers were found using the reported search, of which one presented the best evidence to answer the clinical question. The author, date, and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of this best paper are tabulated. A clinical bottom line is stated.